Highly flexible Fe2O3/TiO2 composite nanofibers for photocatalysis and utraviolet detection. (October 2018) - Liu, Hui; Zhang, Zhi-Guang; Wang, Xiao-Xiong; Nie, Guang-Di; Zhang, Jun; Zhang, Shan-Xiang; Cao, Ning; Yan, Shi-Ying; Long, Yun-Ze
Abstract: Highly flexible Fe2 O3 /TiO2 composite nanofibers were successfully synthesized via electrospinning followed by high-temperature calcination. The morphologies and structures of Fe2 O3 /TiO2 nanofibers were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and ultraviolet-visible (UV-Vis) spectroscopy, and their optical properties, photocatalysis and photodetection properties were also measured. The flexible nanofibers possess large specific surface area, and can be recycled by a magnet. Moreover, the absorption region has been extended from the UV region to the visible region, improving the performance of photocatalyst under visible light radiation. In addition, the formation of Fe2 O3 /TiO2 heterostructures suppresses the recombination of photogenerated electron-hole pairs, which also improves the photocatalyst behavior. Particularly, these nanofibers can also work as a sensitive UV detector, which offers in situ monitor method of such photocatalysis materials. Highlights: The Fe2 O3 /TiO2 nanofibrous membranes exhibited a new flexible inorganic nanofibers system. The magnetic properties of Fe2 O3 /TiO2 nanofibers play an important role in the subsequent recovery of photocatalysts. The formation of Fe2 O3 /TiO2 heterostructures improved the photocatalyst behavior. The Fe2 O3 /TiO2 nanofibers offered in situ monitor method for UV detection.